2020
DOI: 10.1364/ao.391103
|View full text |Cite
|
Sign up to set email alerts
|

High-precision THz-TDS via self-referenced transmission echo method

Abstract: Terahertz time-domain spectroscopy (TDS) is a powerful characterization technique which allows for the frequency-dependent complex refractive index of a sample to be determined. This is achieved by comparing the time-domain of a pulse transmitted through air to a pulse transmitted through a material sample; however, the requirement for an independent reference scan can introduce errors due to laser fluctuations, mechanical drift, and atmospheric absorption. In this paper, we present a method for determining co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In fact, an echo signal from the sample measurement, when compared with the direct transmitted signal from the same transmission-mode scan, can lead to the retrieval of sample properties without the need for the standard reference scan. Very recently, this type of reference-free methodology has been applied to determine the refractive index and wave impedance of dielectrics [15].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, an echo signal from the sample measurement, when compared with the direct transmitted signal from the same transmission-mode scan, can lead to the retrieval of sample properties without the need for the standard reference scan. Very recently, this type of reference-free methodology has been applied to determine the refractive index and wave impedance of dielectrics [15].…”
Section: Introductionmentioning
confidence: 99%
“…The lithium niobate slab is modeled with frequencydependent values of complex refractive index, which we have measured via THz TDS, and reported in detail previously. [52] The graphene conductivity (σ) and scattering time (τ) are calculated from the Kubo equations [53] as shown in Equation ( 1) and ( 2), respectively…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The lithium niobate slab is modeled with frequency‐dependent values of complex refractive index, which we have measured via THz TDS, and reported in detail previously. [ 52 ] The graphene conductivity ( σ ) and scattering time ( τ ) are calculated from the Kubo equations [ 53 ] as shown in Equation () and (), respectivelyσ=ie2EnormalFπ2(ω+i/τ)τ=EnormalFμevnormalF2where e is the electron charge, t is the graphene thickness (1 nm), ω is the radial frequency, μ is the graphene charge carrier mobility, and v F is the Fermi velocity (10 8 cm s −1 ).…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Recently, it has been shown that it is also possible to perform reference-free extraction of dielectric and electrical properties of substrates and thin conducting films from THz-TDS measurements [28,29]. This is achieved by comparing individual transients from only the sample waveform, which means that the reference measurement can be omitted and furthermore decreases errors from signal fluctuations originating from the measurement setup such as timing jitter [26], periodic sampling errors [30], and uneven stage movement.…”
Section: Thz-tds Measurement Schemesmentioning
confidence: 99%